The Torch Parade Tradition of the Islamic New Year: A Study of Living Hadith with a Structural-Functional Approach in Ciwedus Village - Aisyah Nur Hasna; Muhammad Alif (el-Sunnah: Jurnal Kajian Hadis dan Integrasi Ilmu, 2026)
The torch parade tradition in Islamic New Year celebrations is a religious-cultural practice that persists in Indonesian Muslim communities, including in Ciwedus Village, Cilegon City. This study addresses two questions: what are the distinctive characteristics of the torch parade in Ciwedus, and how does the ontology of living hadith operate within this tradition through a structural-functional approach. This study employs a qualitative field research method. Data were collected through non-participant observation, semi-structured interviews with religious leaders, community leaders, committee members, and residents, and analyzed through data reduction, presentation, and conclusion drawing with source triangulation. The results show that the Ciwedus torch parade is conducted collectively on the eve of 1 Muharram, involving all segments of society, and is understood not as mahdhah worship but as a local cultural tradition filled with Islamic values. Four hadith values are actualized in concrete social practices: niyyah (intention) is reflected in communal prayer and self-reflection; hijrah manifests in the moral development of youth through active participation; ukhuwah is embodied in communal cooperation throughout the event; and the hadith on tasyabbuh serves as a moral guideline to keep the tradition within Islamic boundaries. This study concludes that the torch parade demonstrates how hadith values are internalized and reproduced through local cultural practice, social participation, and intergenerational transmission of religious identity